Research Progress of Fe-SMA in Seismic Resistance and Durability Enhancement of Bridge Structures - Li, Zezhong; Wen, Zhihao (Transactions on Environment, Energy and Earth Sciences, 2026)
Iron-based shape memory alloys (Fe-SMA) have become a research hotspot in the field of bridge engineering due to their advantages such as shape memory effect, superelasticity and low cost. Due to the difficulty of traditional bridge materials in meeting both seismic resistance and durability requirements, this paper reviews the key performance of Fe-SMA application and the existing research gaps, providing a reference for future related research. This article mainly summarizes the seismic application forms of Fe-SMA in key parts of bridges and analyzes the seismic mechanism of this material regarding shape memory effect and superelasticity. Meanwhile, the research progress of Fe-SMA in enhancing the durability of bridge structures, such as fatigue resistance and corrosion resistance, was expounded. Previous studies have shown that Fe-SMA cannot only effectively enhance the seismic performance of bridges, but also has excellent fatigue resistance and corrosion resistance, which is expected to significantly extend the service life of bridges. There are still deficiencies in the research on Fe-SMA in enhancing the seismic resistance and durability of bridge structures. If it can be studied and improved in the future, it is expected to create tremendous value.
Keywords: Iron-based shape memory alloys (Fe-SMA); Shape memory effect; Bridge; Seismic resistance; Durability.